Diseño de un modelo de gestión por procesos para la implementación de una nueva modalidad de ventas públicas mediante internet, para Comercial Avila Ochoa Compañía Limitada. Año 2013. - Avila Vasquez, Juan Pablo (2014)
In this thesis, a process management model for the implementation of a new focused sales method through internet to the public sector has been designed for Comercial Avila Ochoa Cía. Ltda., Year 2013. The methodology to follow is the identification, sequence and description of the processes, monitoring and improving of different identified processes. This methodology is developed in accordance with general aspects of the company Comercial Avila Ochoa Cía. Ltda., mainly with its mission, vision and values that conform it. The management of the necessary processes for the implementation of a new focused sales method to the public sector, under study, is distributed in the identification, sequence and description of processes, including: To register as a provider to the state, training on procurement, recruitment processes, development of new offers on the market, monitoring and tracking of processes previously developed, and improvement of the identified processes